Does the increase in body weight change the knee and ankle joint loading in walking and running? - Wu, Claire HY (2015)
Previous obese studies showed that there is a correlation of weight to joint load in the knee joint during walking. In load-carrying studies, there are several studies but no consistent findings in the knee joint loads in walking and running.